Characteristics of Four Agricultural Crops Established as Northern Bobwhite Brood Habitat - Denise A. Maidens; John P. Carroll (National Quail Symposium Proceedings, 2017)
Small plots of agricultural crops are often planted in the Southeast for northern bobwhite (Colinus virginianus) management. Often these are viewed as primarily winter habitat, and assumed to provide summer habitat. We evaluated the macroinvertebrate and vegetative structure of millet, sorghum, wheat, and soybean plots on a cotton farm to assess their value as bobwhite brood habitat. During June and July 1999 and June, July, and August 2000, we studied 5 blocks, each planted with all 4 agricultural crops. We measured invertebrate abundance along a 15-meter transect in each plot using vacuum sampling and height/density of vegetation. Visual obstruction readings (VOR) were highest in millet and sorghum, followed by wheat and then soybean (P < 0.001). Macroinvertebrate numbers differed among cover types (P < 0.001), but macroinvertebrate weights did not (P = 0.14). Among important Orders, Coleoptera, Hemiptera, Diptera, and Homoptera were found in greater numbers in millet. Numbers of Hymenoptera did not differ among crops. In most cases, millet yielded the highest biomass and numbers of macroinvertebrates, followed by sorghum. Soybeans and wheat had fewer macroinvertebrates among the crops studied. On our study area it appears that millet provides the best brood habitat, although sorghum appears to provide a second useful crop. Thus, among these crops we recommend use of millet plots as brood habitat for northern bobwhite chicks.
Keywords: agriculture; brood habitat; Colinus virginianus; Georgia; insects; macroinvertebrates; millet; northern bobwhite; sorghum; soybean; wheat